2020
DOI: 10.5194/tc-2020-100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New insights into the drainage of inundated Arctic polygonal tundra using fundamental hydrologic principles

Abstract: Abstract. The pathways and timing of drainage from inundated ice-wedge polygon centers in a warming climate have important implications for carbon flushing, advective heat transport, and transitions from carbon dioxide to methane dominated emissions. This research helps to understand this process by providing the first in-depth analysis of drainage from a single polygon based on fundamental hydrogeological principles. We use a recently developed analytical solution to evaluate the effects of polygon aspect rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In addition, particular regions of discontinuous permafrost are entirely encircled by unfrozen ground. Another important issue in continuous permafrost environment is microtopography which can control the water balance and initiate terrestrial water drainage and discharge to the surface (Liljedahl et al, 2012;Liljedahl et al, 2016;Painter et al, 2016;Harp et al, 2020;Nitzbon et al, 2020;Painter et al, 2023). Ice-wedge polygons are examples of these kind of feature and commonly occur in polygonal tundra that occupies around 30% of the Arctic land.…”
Section: Principal Definitionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, particular regions of discontinuous permafrost are entirely encircled by unfrozen ground. Another important issue in continuous permafrost environment is microtopography which can control the water balance and initiate terrestrial water drainage and discharge to the surface (Liljedahl et al, 2012;Liljedahl et al, 2016;Painter et al, 2016;Harp et al, 2020;Nitzbon et al, 2020;Painter et al, 2023). Ice-wedge polygons are examples of these kind of feature and commonly occur in polygonal tundra that occupies around 30% of the Arctic land.…”
Section: Principal Definitionsmentioning
confidence: 99%
“…These features of lowland tundra have an effect on suprapermafrost groundwater seepage into surface-water drainage channels. Transport of nutrients through the shallow groundwater fluxes into surface is greatly affected by ice-wedge polygons (Helbig et al, 2013;Harp et al, 2020). Furthermore, surface surveys conducted and data collected form remote sensing technique revealed that dramatic alteration of polygonal tundra occurred over the last decades (Liljedahl et al, 2016).…”
Section: Principal Definitionsmentioning
confidence: 99%
See 3 more Smart Citations